Firm Dynamics and Employment Protection: Evidence from Sectoral Data - Anna Bottasso; Maurizio Conti; Giovanni Sulis (Institute for the Study of Labor (IZA), 2016)
In this paper we analyse the impact of employment protection legislation (EPL) on firms' entry and exit rates for a large sample of industries of thirteen countries selected from the most recent version of the OECD Structural and Business Statistics Database. Using a differences-in-differences identification strategy, we find that more stringent EPL is associated to lower entry and exit rates, particularly in industries characterized by higher job reallocation intensity. We also find that both collective and individual dismissal regulations reduce firms' entry and exit rates. Interestingly, our results suggest that the negative effects of EPL is stronger in the case of firms between one and nine employees while, in the case of larger ones, results are not clear-cut. An extensive sensitivity analysis confirm the robustness of our findings.
Keywords: J65; L11; L26; 330; entry and exit; turnover; employment protection legislation; reallocation